Le gaz naturel du bassin du Levant et Chypre : bienfait ou problème ? - Joëlle Dalègre (Cahiers Balkaniques)
The discovery over the past decade of significant natural gas resources in the Levantine basin between Cyprus, the Middle East Coast and Egypt has raised important hopes in riparian States, including Cyprus. But they gave way very quickly to difficulties: who owns the resources of the continental shelf? And if this problem is solved, how to transport this gas to consumers and in what form? In Cyprus, these issues have become major problems, given the current political situation of the island, which is itself embedded in the Greco‑Turkish dispute. Today, they cause serious tensions in the eastern Mediterranean. This is the subject of this article.